Pengaruh model value clarificatuion technique pada materi pantun nasihat terhadap perilaku peduli lingkungan peserta didik kelas v sekolah dasar - Febriyani, Icha Febriyani; Rukayah, Rukayah Rukayah; Yulisetiani, Septi Yulisetiani (Didaktika Dwija Indria, 2025)
This research was conducted to determine the effect of using the VCT (Value Clarification Technique) model in advice rhyme material on the environmental care behavior of grade 5 elementary school students. The method used is a quantitative design with One-Group PreTest-PostTest Design. This research was conducted to assess whether the application of the VCT Model through advice rhyme material has a significant influence on students' environmental care behavior. Apart from that, this research also aims to compare the average environmental care behavior of students who use the VCT model in rhyme advice material with those who do not. It is hoped that the research results will provide a better understanding of the VCT model in increasing environmental care behavior among grade 5 elementary school students. It is also hoped that this research can provide input for teachers regarding the use of advice rhyme material in the learning process. Thus, this research has important implications in developing more effective learning models in the field of environmental care behavior skills at the basic education level